Предмет: Математика,
автор: tsarmangustov
Раскрой скобки и упрости выражение:
−6(4−a)+3(−3a−3)−6(−9+a)
Ответы
Автор ответа:
1
Ответ:
21-9а
Пошаговое объяснение:
-6(4-а)+3(-3а-3)-6(-9+а)=
=6а-24-9а-9+54-6а=
=21-9а
Автор ответа:
0
Ответ:
-6(4-а)+3(-3а-3)-6(-9+а)
-24+6а-9а-9-54-6а
6а-9а-6а-54-9-24
-9а-92
Похожие вопросы
Предмет: Русский язык,
автор: anya8990
Предмет: Русский язык,
автор: zueltor
Предмет: Русский язык,
автор: 01234567890987654
Предмет: Математика,
автор: миражсмиражом
Предмет: Алгебра,
автор: mashadiegel